PENGARUH PENAMBAHAN LABU KUNING (Cucurbita moschata) dan Ikan Gabus (Ophiocephalus striatus) TERHADAP MUTU ORAGNOLEPTIK, KADAR PROTEIN DAN VITAMIN A BISKUIT - Putri Aulia Arza; Sepni Asmira (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Nutrition potential and availability of pumpkin and cork in Indonesia are abundant, so diversification of pumpkin and cork fish in biscuit making is expected to be a more nutritious food alternative. This study was an experimental study using a complete randomized design consisting of three treatments, one control and two replications. This study was conducted in January - June 2016. Observations were made on organoleptic characteristics and protein content of biscuits. The subjective observation result using organoleptic test showed that the level of panelist's preference for color and texture was on treatment A (control) without the addition of pumpkin and cork fish. As for the aroma and taste with the best result is on the treatment of C with the ratio of pumpkin and cork fish (20 g: 20 g). The highest protein content was found in D treatment with the addition of pumpkin and cork fish (30 g: 30 g). Based on the results of research conducted, the addition of yellow squash and cork fish affect the color of biscuits and protein content of biscuits.